Lu Xun and evolution - Pusey, James Reeve, 1940- (SUNY series in philosophy and biology., 1998)
"This book studies one of the most important figures in modern Chinese intellectual history, China's greatest modern writer, Lu Xun (1881-1936). His trenchant criticisms of the China of his day still speak directly to what can be called, without hyperbole, the current crisis in philosophical and political thought in the People's Republic. It is also a study of a non-Western intellectual's struggle - in a time of crisis - to make practical sense of the "Darwinian Revolution," a revolution not limited to the West." "Although Lu Xun died more than sixty years ago, his work is still alive in China (more so than any American writer of the 1920s and 1930s is in the United States). He is viewed paradoxically as both an official icon and as a patron saint of dissent. This book is, therefore, about Lu Xun both in his lifetime and in his second lifetime - and it looks to his third. But it is not just about Lu Xun. It is about Lu Xun and evolution. As a philosophical critique of Lu Xun's thought, it looks to Lu Xun's struggle to make practical sense of evolution, a contradiction that forces "either/or" question on the Chinese, and on us all."--Jacket